Mutations associated with egg adaptation of influenza A(H1N1)pdm09 virus in laboratory based surveillance in China, 2009-2016 - Lei Yang; Yanhui Cheng; Xiang Zhao; Hejiang Wei; Minju Tan; Xiyan Li; Wenfei Zhu; Weijuan Huang; Wenbing Chen; Jia Liu; Zi Li; Yuelong Shu; et al. (Elsevier, 2019)
Mutations of influenza virus associated with adaptation occurring during passage in embryonated chicken eggs could result in antigenic change or reduced vaccine effectiveness. In this study, we investigated the mutations of influenza A(H1N1)pdm09 egg isolates from the Chinese National Influenza Surveillance Network between 2009 and 2016. Thirteen mutations were identified in the hemagglutinin (HA) protein from viruses passaged in eggs, in comparing to those in cells. After scanning public database, four mutations, D127E, L191I, D222G/N and Q223R in HA1, which may alter the receptor-binding specificity, were observed frequently. Although the A(H1N1)pdm09 virus has evolved in human for nearly ten years, most egg-cultured viruses acquired one or more further mutations. Using the egg isolates for influenza surveillance requires extra caution because of these selected mutations, and their impacts on antigenicity and receptor-binding property need further evaluation. Currently, most of the influenza vaccines are produced using egg isolates, particularly in China. Thus, there is an urge to promote the establishment of an alternative influenza vaccine production platform.